Effect of different air-abrasion particles on metal-ceramic bond strength - Tolga Külünk; Murat Kurt; Çağrı Ural; Şafak Külünk; Seniha Baba (Elsevier, 2011)
Background/purpose: Chipping and delaminating of veneering ceramics are critical problems in the fabrication of metal-ceramic restorations. The purpose of this study was to evaluate the effect of different air-abrasion particles on the shear bond strength of a ceramic to nickel-chromium (Ni-Cr) and cobalt-chromium (Co-Cr) alloys. Materials and methods: Forty square specimens (10 mm × 10 mm × 1.5 mm) were cast for each Ni-Cr and Co-Cr alloys. Specimens were divided into four groups for the air-abrasion procedures: 50-μm aluminum oxid particles (Al2O3), 110-μm Al2O3 particles, 30-50-μm synthetic diamond particles, and 60-80-μm cubic boron nitride particles. After the air-abrasion procedures, specimens received ceramic veneering. The shear bond strength was determined at a crosshead speed of 1 mm/min. Data were statistically analyzed by a 2-way analysis of variance with post-hoc Tukey's test (α = 0.05). Effects of the air-abrasion particles on each alloy were examined with a scanning electron microscope. Results: The highest bond strengths were obtained with application of air abrasion with 110-μm Al2O3 particles and the lowest bond strengths were obtained with 50-μm Al2O3 particles (P < 0.05). Conclusions: None of the tested alternative air-abrasion particles provided superior bond strengths compared with 110-μm Al2O3 particles.